Role of high-fat diet on the effect of pioglitazone and melatonin in a rat model of breast cancer - Bojková, Bianka; Orendáš, Peter; Kajo, Karol; Kubatka, Peter; Výbohová, Desanka; Bálentová, Soňa; Kružliak, Peter; Zulli, Anthony; Demečková, Vlasta; Péč, Martin; Adamkov, Marián (European journal of cancer prevention, 2016)
The risk of cancer may be modulated by drugs with pleiotropic effects and diet has been implicated in the efficacy of treatment. The oncopreventive effects of the antidiabetic drug pioglitazone (PIO) and the anti-insomnia drug melatonin (MT), in vivo, have been proven before, but using a standard-type diet. This study evaluated the impact of a high-fat diet on their efficacy in chemically induced mammary carcinogenesis in Sprague-Dawley rats. Mammary tumours were induced by N-methyl-N-nitrosourea (50 mg/kg, intraperitoneal, on the 41st postnatal day). PIO and MT administration was initiated 11 days before the carcinogen application and lasted until the termination of the experiment at 16 weeks. PIO was administered in a diet (10% fat) at a concentration of 100 ppm and MT was administered in tap water (20 mg/l). PIO, MT and the combination did not significantly alter the basic tumour growth parameters. However, histopathology showed a decrease in the high-grade/low-grade tumour ratio, particularly in animals that received combined treatment (P<0.01). Semiquantitative immunohistochemistry indicated the proapoptotic effect of chemoprevention, particularly in the drug combination group (P<0.01), but no changes in tumour cell proliferation and angiogenesis were recorded. Results were evaluated by one-way analysis of variance or the Mann-Whitney U-test, respectively. PIO and MT, alone or in combination, administered to rats fed a high-fat diet reduced the proportion of high-grade tumours and promoted apoptosis in an in-vivo breast cancer model, although it did not suppress tumour growth. The impact of high dietary fat content on the chemopreventive efficacy of these and other substances should be considered in human studies.
Keywords: modely nemocí na zvířatech; antioxidancia; methylnitrosomočovina; experimentální nádory mléčných žláz; potkani Sprague-Dawley; Mammary Neoplasms, Experimental; kombinovaná farmakoterapie; thiazolidindiony; Diet, High-Fat; dieta s vysokým obsahem tuků; melatonin; Drug Therapy, Combination; Pioglitazone; Melatonin; krysa rodu Rattus; Thiazolidinediones; hypoglykemika; Animals; ženské pohlaví; Antioxidants; Carcinogens; pioglitazon; karcinogeny; Methylnitrosourea; zvířata; Rats; Disease Models, Animal; Hypoglycemic Agents; Female; Rats, Sprague-Dawley